A Split-face comparison of ablative fractional lasers (CO2 and Er:YAG) in Asian patients; postprocedure erythema, pain and patient's satisfaction. (April 2013) - Jung, Kyung Eun; Jung, Kum Hee; Park, Young Min; Lee, Jun Young; Kim, Tae Yoon; Kim, Hyung Ok; Kim, Hei Sung
Abstract Fractional photothermolysis has become popular in the recent years and is currently widely used for the treatment of scars and for photo-rejuvenation purposes. The fractional photothermolysis is to thermally alter a 'fraction' of the skin, leaving intervening areas of normal skin untouched, which rapidly repopulate the altered columns of tissue. Fractional photothermolysis is subdivided into non-ablative and ablative fractional resurfacing. Ablative fractional resurfacing uses fractional CO2 or Er:YAG lasers to create deeper columns of thermal damage.Few studies have compared fractional CO2 and Er:YAG lasers on scars and cutaneous photodamages by a split trial. In this pilot study, we have compared the effects, down time, postprocedure erythema, pain of CO2 and Er:YAG fractional lasers using analysis of clinical photographs, dermoscopic findings and patient's rate of satisfaction.